2008
DOI: 10.1111/j.1365-2621.2007.01554.x
|View full text |Cite
|
Sign up to set email alerts
|

Technological effect of red grape antioxidant dietary fibre added to minced fish muscle

Abstract: The aim was to study the effect, over 6 months in frozen storage, of addition of grape antioxidant dietary fibre (GADF) to horse mackerel (Trachurus trachurus) minced muscle (MFM) as a technological ingredient. Concentrations of 0, 2 and 4% GADF were added to MFM samples. Protein solubility, water retention, colour, mechanical properties, lipid oxidation and sensory analyses were carried out immediately after preparation of samples and during and after storage at )20°C. Bound water after thawing and cooking mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 53 publications
7
34
1
Order By: Relevance
“…2C and D) and causing the products to be softer (Table 5). Similar results have been reported in minced fish with added grape dietary fibre (Sanchez-Alonso & Borderias, 2008) and in patties with wheat flour (Fernández, 1997).…”
Section: Microstructuresupporting
confidence: 89%
See 1 more Smart Citation
“…2C and D) and causing the products to be softer (Table 5). Similar results have been reported in minced fish with added grape dietary fibre (Sanchez-Alonso & Borderias, 2008) and in patties with wheat flour (Fernández, 1997).…”
Section: Microstructuresupporting
confidence: 89%
“…Others (Chun et al, 1999) have found no differences in the texture of patties with seaweed powder added. Others again have reported softer products with the addition of 2.5% and 5% inulin powder in the case of low-fat sausages (Selgas, Cáceres, & García, 2005) and grape dietary fibre in the case of minced fish muscle (Sanchez-Alonso & Borderias, 2008).…”
Section: Texturementioning
confidence: 97%
“…Sánchez-Alonso et al (2007b) found that there was a decrease in the ratio of SSP in horse mackerel mince when the amount of white-grape DF concentrate was higher. This finding concurs with that of Sánchez-Alonso and Borderías (2007) and Sánchez-Alonso et al (2007a) in which red grape dietary concentrate and wheat DF were added to minced fish. According to Sánchez-Alonso and Borderías (2007), a possible explanation for the lower values found in the SSP could be that DF by itself is able to form fiber/protein aggregates large enough to resist extraction.…”
Section: Statistical Analysessupporting
confidence: 93%
“…moreover, Tseng and Zhao (2013) reported an increase in synaeresis in yogurt samples added more than 3% wine grape pomace. Also a study by Diaz-Rubio et al (2009) showed that the addition of Fucus ADF to fish mince did not cause a significant difference in retained water after thawing compared to the results obtained by Sanchez-Alonso and Borderias (2008), who added GADF to the same product. This information might show that properties like water retention, holding and binding capacities are likely to be dependent on the food product and the type of ADF added.…”
Section: Adf As a Technological Ingredientmentioning
confidence: 84%